UTILIZATION OF CCTV AS STUDENT CHARACTER DEVELOPMENT MEDIA IN MUHAMMADIYAH JUNIOR HIGH SCHOOL KAMPUNG PISANG LABUHAN HAJI - Sudarmadi; Mayang Sari; Akmaluddin; Mardhatillah (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Many schools have installed CCTV but have only used it for security purposesand have not used it optimally for the formation and development of studentcharacter. This type of research is qualitative research with a descriptiveanalysis method regarding the implementation of the use of CCTV as a mediumfor the formation and development of student character at SMPMuhammadiyah Kampung Pisang Labuhanhaji. Data collection was carried outusing interviews, questionnaires, observation, and document studies, whiletesting the validity of the data using technical triangulation and sourcetriangulation. The results of the study showed that (1) the formation ofdiscipline,orderliness, student punctuality and security at SMPMuhammadiyah Kampung Pisang Labuhanhaji increased after CCTV wasinstalled. (2) The effectiveness of CCTV surveillance in improving thecharacter of Muhammadiyah Middle School students in Kampung PisangLabuhanhaji has been quite effective. Improvements that need to be made tomaximize CCTV as a means of building student character are inappropriateactions from students immediately followed up on the spot and adding CCTVmonitors so that more are not only Principals, BK Teachers, and Student Affairswho use CCTV as monitoring media but more parties who can supervisestudent behavior in the context of character building.